HUBUNGAN LINGKUNGAN SEBAGAI SUMBER BELAJAR DAN MOTIVASI MAHASISWA DALAM MENINGKATKAN MINAT DAN HASIL BELAJAR PADA MATA KULIAH MORFOLOGI TUMBUHAN DI SEKOLAH TINGGI KEGURUAN ILMU PENDIDIKAN ITA WOTU NUSA (STKIP-IWN) BULA - Dina Ismail; Johanis F Rehena; Alwi Smith (BIOPENDIX, 2020)
Background: Learning biology by utilizing the environment as a source of learning means using an environmental approach. An environmental approach is a learning strategy that is carried out by utilizing the environment as a source or teaching material. This study aims to determine the relationship of the environment as a source of learning and student motivation in increasing interest and learning outcomes in the Plant Morphology course at the Ita Wotu Nusa College of Education (STKIP-IWN) Bula. Method: The method used in this study is the quasi-experimental method. The subjects of this study were all biology students in the third semester, totaling 30 students. Data collection techniques were carried out with initial tests, final tests and questionnaires. Data analysis techniques used in this study will be analyzed correlation test with the help of the IBM statistical program version 23.0 for windows. Results: The results showed the relationship of X1 (environment as a source of learning) with Y1 (interest in learning) obtained sig. (2-tailed) 0.024 <0.05 with a correlation coefficient of 0.412 which means that both variables have a positive and significant relationship with the level moderate closeness. The relationship of X1 (environment as a source of learning) with Y2 (learning outcomes) obtained a value of sig. (2-tailed) 0.013 <0.05, with a correlation coefficient of 0.448 which means that the two variables have a positive and significant relationship with moderate levels of closeness . Relationship X2 (learning motivation) with Y1 (learning interest) sig. (2-tailed) 0.018 <0.05 with a correlation coefficient of 0.430, which means that both variables have a positive and significant relationship with moderate levels of closeness. The relationship X2 (learning motivation) with Y2 (learning outcomes) obtained sig. (2-tailed) 0.028 <0.05 with a correlation coefficient of 0.402 which means that both variables have a positive and significant relationship with a moderate level of closeness. The relationship X1 (environment as a source of learning), X2 (motivation to learn) with Y1 (interest in learning) obtained sig. (2-tailed) 0,000 <0.05 with a correlation coefficient of 0.922 which means that the three variables have a positive and significant relationship with a very strong level of closeness. The relationship X1 (environment as a source of learning), X2 (motivation to learn) with Y2 (learning outcomes) obtained sig. (2-tailed) 0,000 <0.05 with a correlation coefficient of 0.918 which means that the three variables have a positive and significant relationship with a very strong level of closeness. Conclusion: The environment as a source of learning and student motivation has a very close relationship in increasing student interest and learning outcomes in the Plant Morphology course at STIKP-IWN Bula.